Colorectal cancer incidence trends by tumour location among adults of screening‐age in England: a population‐based study - Granger, Sam. P.; Preece, Ryan. A. D.; Thomas, Michael. G.; Dixon, Steven. W.; Chambers, Adam. C.; Messenger, David. E. (Colorectal disease, 2023)
Proximal and distal colorectal cancers (CRCs) exhibit different clinical, molecular and biological patterns. The aim of this study was to determine temporal trends in the age-standardized incidence rates (ASIRs) of proximal and distal CRC following the introduction of the English Bowel Cancer Screening Programme (BCSP) in 2006. The National Cancer Registration and Analysis Service database was used to identify incident cases of CRC among adults of screening age (60-74 years) between 2001 and 2017. ASIRs were calculated using the European Standard Population 2013 and incidence trends analysed by anatomical subsite (proximal, caecum to descending colon; distal, sigmoid to rectum), sex and Index of Multiple Deprivation (IMD) quintile using Joinpoint regression software. Between 2001 and 2017, 541 515 incident cases of CRC were diagnosed [236 167 proximal (43.6%) and 305 348 distal (56.4%)]. A marginal reduction in the proximal ASIR was noted from 2008 [annual percentage change (APC) -1.4% (95% CI -2.0% to -0.9%)] compared with a greater reduction in distal ASIR from 2011 to 2014 [APC -6.6% (95% CI -11.5% to -1.5%)] which plateaued thereafter [APC -0.5% (95% CI -3.2% to 2.2%)]. Incidence rates decreased more rapidly in men than women. Adults in IMD quintiles 4-5 experienced the greatest reduction in distal tumours [APC -3.5% (95% CI -4.3% to -2.7%)]. Following the introduction of the English BCSP, the incidence of CRC has subsequently reduced among adults of screening age, with this trend being most pronounced in distal tumours and in men. There is also evidence of a reduction in the deprivation gap for distal tumour incidence. Strategies to improve the detection of proximal tumours are warranted.